Influence of Zn Injection on Corrosion of 304SS Under PWR Primary Side Conditions - Wei, Haibo; Lin, Jingwei; Liu, Zhikun; Wu, Lina; Chi, Lisheng (Frontiers in Materials, 2022)
The structural materials in nuclear power plants experience corrosion under high temperature water chemistry environments, which could result in serious safety issues. Zinc injection to the primary side chemistry has been demonstrated to reduce corrosion rate of the structural materials and radiation dose rate by modifying the oxide film formed on the structural materials. The purpose of this work is to investigate the effect of Zn addition at different concentrations on 304SS under PWR primary side conditions by SEM, GIXRD, Raman spectrum, XPS, electrochemical method and thermodynamic calculation. When Zn concentration is increased, the number and size of Fe-based spinel oxide particles in the outer layer decreases while Cr-based spinel oxide in the inner layer remains unchanged. The corrosion current density of 304SS and defect density of the oxide film decrease with increasing Zn concentration. These results conclude that corrosion resistance of 304SS is enhanced in the presence of Zn. In addition, the thermodynamic analyses on the spinel oxides of surface were performed and the results are in good agreement with the experimental observations presented in this work.